The sexual history of the global South : sexual politics in Africa, Asia and Latin America Author: Wieringa, Saskia, 1950- - Wieringa, Saskia, 1950- (London : Zed Books, 2013., 2013)
The Sexual History of the Global South explores the gap between sexuality studies and post-colonial cultural critique. Featuring twelve case studies based on original historical and ethnographic research in Africa, Asia, and Latin America, the book examines the sexual investments underlying the colonial project and the construction of modern nation-states.